(untitled) (Acta Scientiarum. Animal Sciences, 2015)
This experiment evaluated the effect of molasses with or without microbial additive on soybean silage regarding the intake, digestibility and growth performance of beef cattle. The experimental design used was randomized blocks with four treatments (diets with soybean silage (SS), SS with microbial inoculant, SS with molasses and SS with microbial inoculant and molasses) and seven replications. Animal were feedlot fed for 99 days. Diets contained forage: concentrate ratio of 70:30, the forage consisted of 40% soybean silage and 30% corn silage. There was lower intake of nutrients in the diet containing SS in relation to the SS diet added with inoculant and molasses. The diet containing SS with inoculant and molasses presented higher apparent digestibility for DM, CP, NDF, ADF, and NFC. Feed conversion, average daily gain and carcass gain were not influenced by the diets, with mean values of 5.90; 1.49 and 0,91 kg day-1 respectively. The addition of molasses combined or not with bacterial inoculant to soybean at the time of ensiling has no effect on the performance of beef cattle, although favoring the intake and digestibility of nutrients.